Colonoscopy procedural skills and training for new beginners - Lee, Seung-Hwa (World J Gastroenterol, 2014)
The incidence of colorectal cancer has been increasing in the developed world including South Korea and China. Colonoscopy allows for greater diagnostic specificity and sensitivity compared with other types of examinations, such as the stool occult blood test, barium enema, and computed tomography colonography. Therefore, in recent years, the demand for colonoscopies has grown rapidly. New beginners including primary care physicians may help meet the increasing demand by performing colonoscopies. However, it is a challenge to learn the procedure due to the long learning-curve and the high rate of complications, such as perforation and bleeding, as compared to gastroscopy. Thus, considerable training and experience are required for optimal performance of colonoscopies. In order to perform a complete colonoscopic examination, there were a few important things to learn and remember, such as the position of examinee (e.g., left and right decubitus, supine, and prone) and examiner (two-man method vs one-man standing method vs one-man sitting method), basic skills (e.g., tip deflection , push forward and pull back, torque, air suction and insufflation), advanced skills (e.g., jiggling and shaking, right and left turn shortening, hooking, and slide-by technique), assisting skills (e.g., position change of examinee, abdominal compression, breathing-holding, and liquid-infusion technique), and intubation techniques along the lower gastrointestinal tract. In this article, we attempt to describe the methods of insertion and advancement of the colonoscope to the new beginners including primary care physician. We believe that this article may be helpful to the new beginners who wish to learn the procedure.